2018
DOI: 10.1002/jcop.22115
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sense of community on the relationship between community participation and mental health for individuals with serious mental illnesses

Abstract: The goal of the current study is to better understand the association between community participation and mental health by investigating sense of community as a potential mediating factor between community participation, psychological distress, and mental health functioning. A survey was administered to 300 adults with serious mental illnesses using community mental health services in the United States in a cross‐sectional design. Hayes PROCESS macro (model 4, version 2.16; Hayes, 2013) was employed to test al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…The survey also included the Temple University Community Participation (TUCP) measure, an assessment of participation in 26 areas that asks about how many days the individual participated in each type of activity in the past 30 days, if each activity is important to them (yes/no), and whether they do each activity enough (not enough, enough, or too much). The TUCP has been used previously to measure community participation among adults with serious mental illnesses (Chang et al, 2016;Salzer et al, 2015;Terry et al, 2019). This research has identified differences in community participation across areas of residence (urbanicity) (Townley et al, 2017) and neurocognitive status (Thomas et al, 2019), and has utilized Geographic Information System (GIS) methodology (Townley et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The survey also included the Temple University Community Participation (TUCP) measure, an assessment of participation in 26 areas that asks about how many days the individual participated in each type of activity in the past 30 days, if each activity is important to them (yes/no), and whether they do each activity enough (not enough, enough, or too much). The TUCP has been used previously to measure community participation among adults with serious mental illnesses (Chang et al, 2016;Salzer et al, 2015;Terry et al, 2019). This research has identified differences in community participation across areas of residence (urbanicity) (Townley et al, 2017) and neurocognitive status (Thomas et al, 2019), and has utilized Geographic Information System (GIS) methodology (Townley et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In summary, several studies have found significant associations: (a) between SOC with depression and mental illness (Li et al, 2011; Huang et al, 2016; Terry et al, 2019); (b) SOC and good health (Carpiano and Hystad, 2011; Johnson et al, 2011; Anderson et al, 2016); as well as, (c) SOC and life satisfaction (Farrell et al, 2004; Kutek et al, 2011; Huang and Wong, 2014; Ng and Fisher, 2016; Yao et al, 2018; Rugel et al, 2019).…”
Section: Sense Of Community (Soc) Well-being and The Health Of Immigmentioning
confidence: 98%
“…Among military spouses, SOC has been examined as a mediator: (a) between social support and psychological well−being (Wang et al, 2015); (b) between social support and participation in youth−based community organizations, and outcomes relevant to adolescent development (Lardier et al, 2019); (c) between the transgender identity and overall well−being (Barr et al, 2016). Terry et al (2019) found that SOC is an important mediator of community participation and mental health. Despite the importance of these findings, among immigrants, few studies have been conducted that analyze the mediating effects of SOC on physical health and mental well-being.…”
Section: Sense Of Community (Soc) Well-being and The Health Of Immigmentioning
confidence: 99%
“…Chaudhry and Li (2011) stated that Muslims in the United States are more likely to have mental health issues than are any other minority groups because of the challenging psychosocial issues that they encounter. Terry, Townley, Brusilovskiy, and Salzer (2018) found that sense of community is an important mediator for community participation and psychological distress, which means mental health functioning.…”
mentioning
confidence: 99%
“…Therefore, many researchers have emphasized focusing on collaboration with the community to identify the most common primary concerns (e.g., Abe et al, 2018;Becker, Reiser, Lambert, & Covello, 2014;Francisco, 2013;Francisco & Butterfoss, 2007;McMillan & Chavis, 1986;Terry et al, 2018). This would ensure that Muslims' needs are met and that they get familiarized with formal mental health services in an effective way so that their issues are addressed and their quality of life is enhanced, as mental health services include both (Kaplan, Tarvydas, & Gladding, 2014).…”
mentioning
confidence: 99%